From Bioinactive ACTH to ACTH Antagonist: The Clinical Perspective - Ghaddhab, Chiraz; Vuissoz, Jean-Marc; Deladoëy, Johnny (Frontiers in Endocrinology, 2017)
The adrenocorticotropic hormone ACTH is a pituitary hormone derived from a larger peptide, the proopiomelanocortine (POMC), as are the MSHs (α-MSH, β-MSH and γ-MSH) and the β-LPH-related polypeptides (Figure 1A). ACTH drives adrenal steroidogenesis and growth of the adrenal gland. ACTH is a 39 amino acids polypeptide that binds and activates its cognate receptor (melanocortin receptor 2, MC2R) through the two regions H6F7R8W9 and K15K16R17R18P19. Most POMC-derived polypeptides contain the H6F7R8W9 sequence that is conserved through evolution. This explains the difficulties in developing selective agonists or antagonists to the melanocortin receptors. In this review, we will discuss the clinical aspects of the role of ACTH in physiology and disease, and potential clinical use of selective ACTH antagonists.